Macro Curriculum Analysis on Writing for Professional Context Standardized by CEFR based on the Characteristic of Pekalongan the World Creative City - Inayatul Ulya (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
English learning should follow standardization to show its framework competence. One of them is Common European Framework References (CEFR). Writing for professional context subject is equal with B1 and C2 on assessment grid. This study was aimed in analyzing the need to develop teaching materials of Writing for professional context which was based on CEFR standard and contextualized by Pekalongan characteristic as the World Creative city. The research method which was implemented was descriptive analysis. The subjects of this research were the head of English Department, the writing lecturer, and the second term students of English Department. The instrument of this research was questionnaire. The result showed lecturer’s performance in teaching writing for professional context. Based on the students’ perception, they had high interest on this subject. Meanwhile, for the questionnaire of need analysis developing electronic module, it was open question; all of the students gave positive response. They stated that E-module offers easiness for them, it can be read everywhere and anywhere. It will support the students to learn independently. In addition, it is very effective, efficient and paperless. In addition the content of E-module was agreed for having its own characteristic which raises local wisdom. Therefore, it can be contextualized with the characteristic of Pekalongan the world creative city to the content development of writing material, especially text types.Keywords: Macro Curriculum, CEFR, E-module, World Creative City